Вакуумная деазотация металлов – растворителей для синтеза алмаза - Поздняков, А.А.; Бугаков, В.И.; Полушин, Н.И.; Давыдов, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Methods of the vacuum denitration of solvent metals (Ni, Fe), used in the diamond synthesis, are suggested in the work. It has been experimentally determined that the given methods of the purification of Ni and Fe make it possible to reduce the concentration of nitrogen in metals up to 0,0002% mass.